Payments and Utilization of Immunization Services Among Children Enrolled in Fee-for-Service Medicaid - Tsai, Yuping (Med Care, 2018)
OBJECTIVE: To examine the association between state Medicaid vaccine administration fees and children’s receipt of immunization services. METHODS: The study used the 2008–2012 Medicaid Analytic eXtract data and included children aged 0–17 years and continuously enrolled in a Medicaid fee-for-service plan in each study year. Analyses were restricted to 8 states with a Medicaid managed-care penetration rate <75%. Linear regressions were used to estimate the probability of children making ≥1 vaccination visit and the numbers of vaccination visits in the year as a function of state Medicaid vaccine administration fees, age group, sex, race/ethnicity, state unemployment rate, state managed-care penetration rate, and state and year-fixed effects. RESULTS: A total of 1,678,288 children were included. In 2008–2012, the average proportion of children making ≥1 vaccination visit per year was 31% and the mean number of vaccination visits was 0.9. State Medicaid reimbursements for vaccine administration was positively associated with immunization service utilization; for every $1 increase in the payment amount, the probability of children making ≥ 1 vaccination visit increased by 0.72 percentage point (95% confidence interval, 0.23–1.21; P = 0.01), representing a 2% increase from the mean and the number of vaccination visits increased by 0.03 (95% confidence interval, −0.00 to 0.06; P < 0.1). The estimated effect was greater among younger children. CONCLUSION: Higher Medicaid reimbursements for vaccine administration were associated with increased proportion of children receiving immunization services.